Perancangan Antena Vivaldi Antipodal 2 - 18 GHz untuk Radio Direction Finder - Deri Latika Herda; Siska Aulia; Frenzi Agres Yudithia (Spektral, 2023)
The 2-18 GHz frequency band is a spectrum that is widely used for telecommunication systems, both military and civil. This is proportional to the number of illegal uses. This research develops an antipodal vivaldi antenna to support direction finding activities of illegal transmitters in the 2-18 GHz frequency band. Antenna design is a simulation using CST software by modifying the ground, widening the antenna arm, and increasing the length of the transmission line. The antenna design measures 94.14 x 73.2 mm on FR-4 substrate with a dielectric constant of 4.6 and a thickness of 1.6 mm. The simulation results show that the antipodal vivaldi antenna has a value -49.95378 dB ≤ S11 ≤ -10.022357 dB, 1.0066947≤ VSWR ≤1.9248251 and an average gain of 5.1558 dB in the 2-18 GHz frequency band.